Validity of a new stabilometric force platform for postural balance evaluation. - Jonathan Ache Dias; Lucas Borges; Daniela Junckes da Silva Mattos; Marcelo Diederichs Wentz; Susana Cristina Domenech; Philippe Kauffmann; Noé Gomes Borges Junior (Universidade Federal de Santa Catarina, 2011)
The objective of this study was to validate a new stabilometric force platform (SFP). For this, three steps have been established: a) to determine the force threshold to reach an acceptable level of accuracy of the centre of pressure (CoP) measurement by the application of single point load; b) to determine the accuracy of the CoP measurement in the application of distributed load simulating the human feet; c) to verify the concurrent validity of the SFP by comparing it with a commercial force platform (FP). The tests performed in steps "a" and "b" were conducted by applying loads on the SFP using a universal testing machine. In the application of single point load, the mean force threshold presented by the SFP was 315.6 ± 140.5 N. The CoP measurement error in the points near the centre of the SFP was 1.04 ± 0.80 mm in medial-lateral (ML) and 1.31 ± 0.99 mm in anteriorposterior (AP) direction. In the points near the edges of the plate, the error was 2.03 ± 0.91mm (ML) and 1.54 ± 0.96 mm (AP). In the test with distributed loads, errors of less than 1mm were found. Additionally, no differences were found in the CoP parameters between SFP and the FP. The CoP measurement signal presented high correlation between both equipments in AP (r = 0.997 ± 0.001) and ML (r = 0.988 ± 0.003) directions. These findings suggest that the SFP can be used in scientific investigations of balance in quiet standing.